The Rhetoric of Silence (Per Musi, 2011)
There is a lack of a single doctrine for the use of rhetoric in baroque music. The rhetorical theory has interpretative and heterogeneous qualities.  In order to reveal some of the aesthetic objectives of the meraviglia, which are focused on provoking a shocking sense of wonderment through creating experiences that astonish with delight, musical examples of the pathetic use of silences are presented. Rhetoric is viewed as the energy inherent in emotion and thought, transmitted through a system of signs, including music, to others with the objective of influencing their decisions and actions.